2012
DOI: 10.1080/09658211.2011.651089
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences for the recognition of direct versus averted gaze faces

Abstract: Gaze direction plays a central role in face recognition. Previous research suggests that faces with direct gaze are better remembered than faces with averted gaze. We compared recognition of faces with direct versus averted gaze in male versus female participants. A total of 52 adults (23 females, 29 males) and 46 children (25 females, 21 males) completed a computerised task that assessed their recognition of faces with direct gaze and faces with averted gaze. Adult male participants showed superior recognitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 28 publications
1
11
0
Order By: Relevance
“…To our knowledge, eye‐tracking methods have not been employed to determine whether or not gaze‐following accounts for the difference between recognition of direct‐ and averted‐gaze faces in typically developing individuals. However, in a recent study of adult control participants, we [Goodman, Phelan, & Johnson, ] employed a centrally located attention probe during the learning phase of this task. We hypothesized that if participants were following gaze on averted gaze trials, detection of probes would be worse and response times would be slower compared with the performance on direct‐gaze trials.…”
Section: Methodsmentioning
confidence: 99%
“…To our knowledge, eye‐tracking methods have not been employed to determine whether or not gaze‐following accounts for the difference between recognition of direct‐ and averted‐gaze faces in typically developing individuals. However, in a recent study of adult control participants, we [Goodman, Phelan, & Johnson, ] employed a centrally located attention probe during the learning phase of this task. We hypothesized that if participants were following gaze on averted gaze trials, detection of probes would be worse and response times would be slower compared with the performance on direct‐gaze trials.…”
Section: Methodsmentioning
confidence: 99%
“…These differences were observed specifically in within-task learning and recognition paradigms 1517 or simultaneous perceptual matching paradigms 6,18,19 , with females showing better performance than males. Further, superior recognition of unfamiliar faces in females has shown to be highly robust and invariant to face view 20 , gaze direction 21 , face-race 22,23 as well as duration of presentation 15,24 . Studies have also reported own-gender biases, with females being consistently better at recognizing female than male faces 6,24,25 and less consistently reported a male own-gender bias 26,27 .…”
Section: Introductionmentioning
confidence: 99%
“…Often eye contact helps all participants recognize a face, regardless of the their gender (Macrae et al., 2002; Hood et al., 2003; Mason et al., 2004; Smith et al., 2006). However, in some contexts, one gender will benefit from eye contact, but the other will not (e.g., Otteson and Otteson, 1980; Goodman et al., 2012; Helminen et al., 2016). Finally, researchers have observed gender differences in how attentive participants are to the eyes (Connellan et al., 2000; Lutchmaya et al., 2002) and the nonverbal signals of others (Hall, 1978; Rosenthal et al., 1979; McClure, 2000), as well as how responsive participants are to these signals (e.g., females maintain more distance between themselves and a virtual agent that makes eye contact than males; Bailenson et al., 2001; Bayliss et al., 2005).…”
Section: Introductionmentioning
confidence: 99%